2009
DOI: 10.1074/jbc.m109.041194
|View full text |Cite
|
Sign up to set email alerts
|

Integrin Activation Dynamics between the RGD-binding Site and the Headpiece Hinge

Abstract: Integrins form mechanical links between the extracellular matrix and the cytoskeleton. Although integrin activation is known to be regulated by an allosteric conformational change, which can be induced from the extracellular or intracellular end of the molecule, little is known regarding the sequence of structural events by which signals propagate between distant sites. Here, we reveal with molecular dynamics simulations of the FnIII 10 -bound ␣ V ␤ 3 integrin headpiece how the binding pocket and interdomain ␤… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
74
1

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 63 publications
(80 citation statements)
references
References 43 publications
5
74
1
Order By: Relevance
“…Integrin activation can be induced by binding molecules inside the cell (inside-out activation) (Puklin-Faucher and Sheetz, 2009), or forces exerted by the ECM and transmitted through ligand (outside-in activation) and a subsequent propagation of conformational changes from the tail to head and head to tail domains, respectively. Some suggest that during cell adhesion, conformational changes are induced simultaneously by inside-out and outside-in signals, and expedited by forces transmitted through ligands (Alon and Dustin, 2007;Puklin-Faucher and Sheetz, 2009;Puklin-Faucher et al, 2006). Simulations by Puklin-Faucher et al show acceleration in activation events from seconds to microseconds in the presence of mechanical forces (PuklinFaucher et al, 2006).…”
Section: Integrin Activationmentioning
confidence: 99%
See 1 more Smart Citation
“…Integrin activation can be induced by binding molecules inside the cell (inside-out activation) (Puklin-Faucher and Sheetz, 2009), or forces exerted by the ECM and transmitted through ligand (outside-in activation) and a subsequent propagation of conformational changes from the tail to head and head to tail domains, respectively. Some suggest that during cell adhesion, conformational changes are induced simultaneously by inside-out and outside-in signals, and expedited by forces transmitted through ligands (Alon and Dustin, 2007;Puklin-Faucher and Sheetz, 2009;Puklin-Faucher et al, 2006). Simulations by Puklin-Faucher et al show acceleration in activation events from seconds to microseconds in the presence of mechanical forces (PuklinFaucher et al, 2006).…”
Section: Integrin Activationmentioning
confidence: 99%
“…Additionally, there is evidence supporting the idea that it is heterodimerization of different integrin molecules that triggers the clustering phenomenon (Luo et al, 2005). Indeed, the challenge on the way of studying transmembrane proteins (e.g., integrin) embedded in the plasma membrane has led researchers to use alternative methods that neglect effects of the plasma membrane on integrin activation/clustering, whereas a major body of molecular level, computational studies of integrin are focused on simulating the ectodomain exclusively (Chen et al, 2011;Puklin-Faucher and Sheetz, 2009;Puklin-Faucher and Vogel, 2009). To reconcile these pieces of apparently contradictory evidence while taking into account effects of the plasma membrane, a series of MD simulation has been recently carried out that underlined the critical role of the plasma membrane in homooligomerization of integrin transmembrane-cytoplasmic domains upon activation .…”
Section: Integrins Team Up (Integrin Clustering)mentioning
confidence: 99%
“…Atomic force microscopy single-bond experiments have demonstrated that ␣ 5 ␤ 1 , an ␣A domain-lacking integrin, forms catch bonds with fibronectin (FN) in which force prolongs bond lifetimes in the 10 -30 pN range (19). Steered molecular dynamics simulations have suggested how force might activate integrin ␣A domains (20) and the headpiece of integrin ␣ V ␤ 3 (21)(22)(23)(24). However, many mechanistic details about the integrin mechanochemistry are still missing.…”
mentioning
confidence: 99%
“…3B) and variables characterizing the bending and splaying of the structure (Fig. 3C, D), which had been used successfully in related studies to characterize inactiveto-active transitions (27,37,64). The results display significant differences in the conformational states of both isoforms of αIIbβ3, with the ectodomain of the Pro33 variant showing a stronger tendency to move towards an open, extended conformation with more splayed legs than the Leu 33 isoform.…”
Section: Discussionmentioning
confidence: 96%